2017
DOI: 10.1016/j.ajic.2017.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Contact tracing with a real-time location system: A case study of increasing relative effectiveness in an emergency department

Abstract: RTLS doubled the potential pertussis exposures beyond EMR-based contact identification. Thus, RTLS may be a valuable addition to the practice of contact tracing and infectious disease monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 21 publications
4
39
0
1
Order By: Relevance
“…Several health care institutions have benefitted from the use of a real-time locating system (RTLS) for contact tracing. Hellmich et al [ 11 ] were able to identify twice as many potential contacts of confirmed pertussis cases in an emergency department with RTLS compared with EMR review. Ho et al [ 12 ] also found that the use of location-based RTLSs to complement EMR review increased the sensitivity of detecting health care workers’ contact with COVID-19 inpatients from 47.2% to 77.8%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several health care institutions have benefitted from the use of a real-time locating system (RTLS) for contact tracing. Hellmich et al [ 11 ] were able to identify twice as many potential contacts of confirmed pertussis cases in an emergency department with RTLS compared with EMR review. Ho et al [ 12 ] also found that the use of location-based RTLSs to complement EMR review increased the sensitivity of detecting health care workers’ contact with COVID-19 inpatients from 47.2% to 77.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Ho et al [ 12 ] also found that the use of location-based RTLSs to complement EMR review increased the sensitivity of detecting health care workers’ contact with COVID-19 inpatients from 47.2% to 77.8%. However, despite the positive outcomes of using RTLSs for contact tracing [ 11 - 13 ], such technologies have largely been confined to health care institutions due to the high costs of infrastructure setup [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each patient is assigned a seat number that is recorded for contact tracing purposes. Contact tracing is also facilitated by a real‐time location system 18 patient tracker tagged to each patient and closed‐circuit television monitoring. Patients are instructed to remain seated and any patient movement within the screening centre is under strict staff supervision.…”
Section: Purpose‐built Infrastructure To Facilitate Patient Flowmentioning
confidence: 99%
“…As the forefront of the efforts in Singapore, the NCID SC operations required secondment of TTSH staff, with urologists among those deployed. The SC assesses patients in terms of travel or contact history [9], respiratory symptoms, fever, suspected or confirmed COVID-19 status, and primary health care referrals. Emergency physicians oversee operations in consultation with infectious disease physicians.…”
Section: Introductionmentioning
confidence: 99%